Deciphering sepsis: transforming diagnosis and treatment through systems immunology - Robert E. W. Hancock; Andy An; Claudia C. dos Santos; Amy H. Y. Lee (Frontiers in Science)
Sepsis is an abnormal, life-threatening response to infection that leads to (multi-)organ dysfunction and failure. It causes ~20% of deaths worldwide each year, and most deaths related to severe COVID-19 share various molecular features with sepsis. Current treatment approaches (antimicrobials and supportive care) do not address the complexity of sepsis or its mechanistic heterogeneity between and within patients over time. Systems immunology methods, including multiomics (notably RNA sequencing transcriptomics), machine learning, and network biology analysis, have the potential to transform the management paradigm toward precision approaches. Immune dysfunctions evident very early in sepsis drive the development of novel diagnostic gene expression signatures (e.g., cellular reprogramming) that could inform early therapy. Sepsis patients can now be categorized into “endotypes” based on unique immune dysfunction mechanisms corresponding to varying severity and mortality rates, raising the prospect of endotype-specific diagnostics and patient-specific immune-directed therapy. Longitudinal within-patient analyses can also reveal mechanisms (including epigenetics) that drive differential sepsis trajectories over time, enabling the prospect of disease stage-specific therapy during and after hospitalization, including for post-sepsis and long COVID syndromes. Achieving this transformation will require addressing barriers to systems immunology research, including its cost and resource-intensiveness, the relatively low volume of available data, and lack of suitable animal models; it will also require a change in the mindset of healthcare providers toward precision approaches. This should be prioritized in multistakeholder collaborations involving research communities, healthcare providers/systems, patients, and governments to reduce the current high disease burden from sepsis and to mitigate against future pandemics.